Croup Associated With SARS-CoV-2: Pediatric Laryngotracheitis During the Omicron Surge. Issue 8 (5th May 2022) - Sharma, Sujit; Agha, Beesan; Delgado, Carlos; Walson, Karen; Woods, Charles; Gonzalez, Mark D; Jerris, Robert; Sysyn, Gregory; Beiter, James; Kamidani, Satoshi; Rostad, Christina A
Abstract: In this retrospective analysis, we describe weekly croup and corresponding viral prevalence patterns in a pediatric quaternary care system in metropolitan Atlanta. We characterize a series of 24 patients with croup associated with SARS-CoV-2 infection and show that this clinical presentation increased substantially in frequency during the period of high Omicron vs Delta transmission.